Predicting Antimicrobial Resistance Using Partial Genome Alignments - D. Aytan-Aktug; M. Nguyen; P. T. L. C. Clausen; R. L. Stevens; F. M. Aarestrup; O. Lund; J. J. Davis (mSystems, 2021)
Antimicrobial resistance causes thousands of deaths annually worldwide. Understanding the regions of the genome that are involved in antimicrobial resistance is important for developing mitigation strategies and preventing transmission.